THE MODEL OF MORAL ESTABLISHING FOR PRIMARY SCHOOL STUDENTS IN NONTHABURI - Kettanom, Thasporn (Academic Journal Phranakhon Rajabhat University, 2021)
The purposes of the study were: 1) to determine the factors and indicators on Moral Establishing Model for the primary school students. ; 2) to propose the Moral Establishing Model for the primary school students in Nonthaburi. The research methodology consisted of four steps: Step 1: analyzing the documents concerning the student morality to set up the conceptual framework; Step 2: developing the factors and indicators with Delphi Technique of 21 experts; Step 3: testing of model agreement on moral establishing to primary school students with a focus group discussion of eight experts; Step 4 evaluating the opinions of 150 school administrators and monks. The analysis of the data was accomplished by the computation of percentage and standard deviation. The median and interquartile ranges were also computed to test the agreement postulated in the study. Research findings of this study, it was concluded that: 1) The Moral Establishing Model for the primary school students for an excellent Thai citizen, the 21 experts agreed with the seven factors and 34 indicators of Moral Establishing Model for the primary school students for an outstanding Thai citizen including diligence, honesty, helpful, discipline, responsibility, democracy and proud to be Thai. 2) The Moral Establishing Model for the primary school students for an excellent Thai citizen, the researcher can conclude as follows: 2.1) Delphi Technique, the 21 experts agreed with the seven factors and 34 indicators of the moral establishing model by considering of median and interquartile. 2.2) Focus Group Discussion, the eight experts also agreed with establishing a moral model for primary school students. 2.3) The evaluation of possibility on the Moral Establishing Model for the primary school students, overall the school administrators and the experts were agreed with high level.